Analysis of the Distribution of Heirth Rights to Adopted Children with Wajibah Testament - Halimahtus Sadiah; Erlina B; Melisa Safitri (Activa Yuris: Jurnal Hukum, 2022)
Adoption of a child is a legal act, because it must have legal consequences. Some of the legal consequences of adopting a child are regarding the position or status of the adopted child as heirs to the adoptive child's parents. Adopted children can not become heirs of adoptive parents, but adopted children have the right to become heirs if the adoptive parents submit a will to the child, this called testament wajibah. The researcher used library research and interview methods. By using this method, the researcher obtained the result that the adopted child could inherit with the determination that it was not more than 1/3 of the inheritance of the adoptive parents. Based on the provisions of Islamic law, adopted children cannot be appointed as heirs, because in the provisions of Islamic law, those who can be appointed as heirs are those who are related by blood to the heir. A will (testament) is different from a gift or what is called a "grant". The difference between a testament and a grant is that a will, even though it has been made when the testator is still alive, is only enforced after the testator has died, while the grant itself is valid when the grantor is still alive.